Simplify.
2x + 6x2
10 + 4x2 – 3x + (-6) =
2 answers:
Answer: 14x,4+4x ^2-3x
Step-by-step explanation:
1. Simplify 6x\times 26x×2 to 12x12x.
2x+12x,10+4{x}^{2}-3x-6
2x+12x,10+4x
2
−3x−6
2 Simplify 2x+12x2x+12x to 14x14x.
14x,10+4{x}^{2}-3x-6
14x,10+4x
2
−3x−6
3 Collect like terms.
14x,((10-6)+4{x}^{2}-3x)
14x,((10−6)+4x
2
−3x)
4 Simplify (10-6)+4{x}^{2}-3x(10−6)+4x
2
−3x to 4+4{x}^{2}-3x4+4x
2
−3x) Hope that helps
God bless you ma’am/sir!!
You might be interested in
I can’t see your question I wish I could help you
Answer:
22 would be your answer.
Answer: The answer is -x+7
Step-by-step explanation:
Multiply the numbers 2 * 2=4
=4x-5x+7
Add similar evidence 4x + -5x =-x
-x+7
Answer:
Step-by-step explanation:
U have to multiply 49 by 49 and then subtract 9
Answer:
9.2
Step-by-step explanation:
first i added 5 + 3 = 8
then i did 1 1/5 + 8=9 1/5